Corporate Governance and Financial Performance: The Role of the Audit Committee in Saudi Arabia: حوكمة الشركات والأداء المالي: دور لجنة المراجعة في المملكة العربية السعودية - Mahrous, Ramadan Aref Ramadan; Moussa , Mahmoud Kamal Araby (Journal of North African Economies, 2025)
This study examines the impact of audit committee characteristics one of the key mechanisms of corporate governance on the performance of companies listed on the Saudi Stock Exchange, Using data from 31 non-financial firms between 2019 and 2022, and firm performance was measured by return on assets. The main variables include audit committee size, meeting frequency, independence, and members’ financial expertise, with firm size and financial leverage serving as control variables, The findings reveal that audit committee independence and meeting frequency are significantly and positively associated with firm performance, whereas committee size and members’ financial knowledge show no significant effect, The study underscores the importance of audit committee characteristics in enhancing governance effectiveness and improving corporate performance within the Saudi context.